Space, place and nonplace in Pere Joan's Passatger en trànsit (1984): forging the Iberian comic in post-dictatorial Barcelona. (3rd July 2021) - Fraser, Benjamin
ABSTRACT: Building on growing interest in the development of the ninth art in Spain, this article returns to a foundational work by creator Pere Joan that encapsulates Barcelona's role in forging the post-dictatorial Iberian comic. Beyond carrying out a close reading of the eponymous comic contained in Passatger en trànsit, it is important also to elucidate the cultural forces shaping post-dictatorial comics in Spain: from the languages of publication, to the legacies of visual style, the relationship between comics and prose literature, and the reemergence of Barcelona as a putative center of the comics industry. Published by Norma Editorial in 1984, the hardback volume arguably reflected the growing expansion of the Catalan-language cultural market specifically and the progressive linguistic diversification of the Iberian comics market in general. The theme, story and comics form of the visual tale – "Passatger en trànsit", which was adapted from English science fiction writer Barrington J. Bayley's earlier short story "Man in Transit" – establish a number of the hallmark traits of Pere Joan's subsequent work: such as contemplative mood; themes of isolation, alienation, interiority and travel; and his characteristic use of landscape panels in page design. The comic's spatial aesthetics also connects with notions of space, place and nonplace that were receiving renewed attention in 1980s Barcelona.